2017
DOI: 10.1353/eca.2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Morbidity in the 21st Century

Abstract: SUMMARYWe build on and extend the findings in Case and Deaton (2015) on increases in mortality and morbidity among white non-Hispanic Americans in midlife since the turn of the century. Increases in all-cause mortality continued unabated to 2015, with additional increases in drug overdoses, suicides, and alcohol-related liver mortality, particularly among those with a high-school degree or less. The decline in mortality from heart disease has slowed and, most recently, stopped, and this combined with the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
851
1
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,063 publications
(903 citation statements)
references
References 42 publications
44
851
1
7
Order By: Relevance
“…In our study, we examined a narrower age group (45 to 54), where increases in a specific group of causes of death (including drug and alcohol poisonings) have been reported (Case and Deaton, 2017). Contrary to expectation, economic downturns almost uniformly lead to improvement in population health indicators (Ruhm, 2008).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, we examined a narrower age group (45 to 54), where increases in a specific group of causes of death (including drug and alcohol poisonings) have been reported (Case and Deaton, 2017). Contrary to expectation, economic downturns almost uniformly lead to improvement in population health indicators (Ruhm, 2008).…”
Section: Resultsmentioning
confidence: 97%
“…This increase was concentrated among nonHispanic whites without a college degree, where mortality increased by 134.4 per 100,000. A more recent analysis by the same authors highlighted the increasing inequalities in mortality by level of education in non-Hispanic white Americans (Case and Deaton, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…What the SDT forecasts for the United States is increasing elite factionalization and polarization, rising state debts, and falling living standards. While that may not lead to the violence of civil war, it is already producing political turmoil and large human costs, including an unusual and striking decline in U.S. life expectancy due to hundreds of thousands of opioid-linked and suicide deaths over the past few years (Case and Deaton 2017). These are arguably casualties of the marked shift of relative income away from wage-earners to the top .1% since the 1980s.…”
Section: Richerson On Ages Of Discordmentioning
confidence: 99%
“…The Organisation for Economic Co-operation and Development has shown that the policy could, perversely, increase inequality and poverty. And, because jobs are so important to our status and self-worth, having money alone does not protect against the increases in morbidity, criminal activity, opioid and alcohol abuse that have been associated with unemployment 12 .…”
Section: Rapid Responsementioning
confidence: 99%